Model Pengembangan Kurikulum Madrasah Hadramaut Di Pondok Pesantren Darul Faqih Malang - Faris Khoirul Anam (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2021)
Model for development of madrasah curriculum hadramaut in pondok pesantren darul faqih malang. This paper provides an overview of the model of Hadramaut Madrasah curriculum development in Darul Faqih Islamic boarding school Malang, starting from constructing the planning, implementation, and evaluation of Hadramaut Madrasah curriculum, theoretically from the concept, to the Darul Faqih Islamic Boarding School. In general, the model of Hadramaut Madrasah curriculum development, which includes planning, implementation, and evaluation, is intended to be carried out in pesantren under the paying of its vision and mission. The Hadramaut education model is a harmonious and moderate education, so that when developed in Islamic boarding schools it can be said to be suitable and appropriate. Although there are many activities carried out in Islamic boarding schools, students can develop their abilities or potential and be bridged to continue their studies at Hadramaut